STRATEGI INVESTASI GENERASI MILENIAL DALAM MASA PEMULIHAN EKONOMI PASCA PANDEMI COVID 19 - Shelvyna Rikantasari; Kholishudin Kholishudin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The research, entitled Millennial Generation Investment Strategy in the Post-Covid-19 Economic Recovery Period, discusses the strategies used by millennials in carrying out investments. This study uses a descriptive qualitative method where the method looks at the actual phenomena that occur in the community so that the resulting research is classified as new research. The results of this study show that millennials are starting to invest in several ways, namely by preparing emergency funds, diversifying wealth and understanding the risks resulting from each investment instrument. With this strategy, millennials are more careful and careful in choosing various investment instruments. This is also directly related to the economy that existed at the time of the COVID-19 pandemic where at that time the economy in Indonesia and other world countries affected by the pandemic experienced a decline in the wheels of the economy. Therefore, the government makes a new normal policy during the pandemic and makes a policy to increase investment with the aim of revitalizing the wheels of the economy that is happening in Indonesia.